New variable stars towards the Galactic Bulge – I. The bright regime. Issue 3 (24th October 2018) - Kains, N; Calamida, A; Rejkuba, M; Bhardwaj, A; Inno, L; Sahu, K C; Zoccali, M; Bono, G; Surot, F; Anderson, J; Casertano, S
ABSTRACT: We report the detection of 3714 variable stars towards the Galactic bulge, including 2521 previously uncatalogued variables, using time-series photometry extracted from data obtained with the VIMOS imager at the Very Large Telescope. Observations of the Sagittarius Window Eclipsing Extrasolar Planet Search (SWEEPS) field in the Galactic Bulge were taken over 2 yr between March and October at a cadence of ∼4 d, enabling the detection of variables with periods up to ∼100 d. Many of these were already known, but we detected a significant number of new variables, including 11 Cepheids, a further 88 potential Cepheid candidates, and many contact binaries. Here we publish the catalogue of the new variables, containing coordinates, mean magnitudes as well as periods and classification; full light curves for these variables are also made available electronically.